Effectiveness of Self-Management Techniques to Improve Learning Independence of Ibnu Katsir 1 Jember Students - Pranata, Ari (Konseling Edukasi : Journal of Guidance and Counseling, 2025)
Effectiveness of Self-Management Techniques to Improve Learning Independence of Ibnu Katsir 1 Jember Students. This study aims to test the effectiveness of self-management techniques in improving student learning independence at Ibnu Katsir 1 Islamic Boarding School in Jember. The background of this study is based on the low level of learning independence identified through initial observations, such as high dependence on teacher direction, lack of initiative in completing assignments, and lack of discipline in managing study time. This study used a quantitative quasi-experimental approach with a one-group pretest-posttest design. The research subjects were 10 students selected based on their low learning independence scores. The data collection technique used a learning independence scale with a validity of ≥ 0.361 and a Cronbach's Alpha reliability of 0.874. Data analysis was carried out using a paired sample t-test with the help of SPSS 26. The results showed an increase in the average learning independence score from a pretest value of 57.3 to 75.6 in the posttest, with a significance value (p) of 0.000 < 0.05. This demonstrates the effectiveness of self-management techniques in enhancing student learning independence. These findings support Bandura's theory of self-reinforcement and social learning and extend its application to the context of Islamic boarding schools. The practical implication of these results is the importance of self-management-based guidance programs in supporting learning independence in Islamic educational environments. Suggestions for future research include expanding the sample size and extending the duration of the intervention to achieve more general and in-depth results.Keywords: Self-management, Learning Independence, Islamic Boarding School.